The growth and migration of massive planets under the influence of external photoevaporation - Winter, Andrew J.; Haworth, Thomas; Coleman, Gavin A L; Nayakshin, Sergei (Monthly notices of the Royal Astronomical Society, 2022)
The formation of gas giant planets must occur during the first few Myr of a star’s lifetime, when the protoplanetary disc still contains sufficient gas to be accreted on to the planetary core. The majority of protoplanetary discs are exposed to strong ultraviolet irradiation from nearby massive stars, which drives winds and depletes the mass budget for planet formation. It remains unclear to what degree external photoevaporation affects the formation of massive planets. In this work, we present a simple one dimensional model for the growth and migration of a massive planet under the influence of external FUV fields. We find that even moderate FUV fluxes $F_FUV\gtrsim 100 \, G_0$ have a strong influence on planet mass and migration. By decreasing the local surface density and shutting off accretion on to the planet, external irradiation suppresses planet masses and halts migration early. The distribution of typical stellar birth environments can therefore produce an anticorrelation between semi-major axis and planet mass, which may explain the apparent decrease in planet occurrence rates at orbital periods Porb ≳ 103 d. Even moderate fluxes FFUV strongly suppress giant planet formation and inward migration for any initial semi-major axis if the stellar host mass $M_*\lesssim 0.5\, {\rm M}_\odot$, consistent with findings that massive planet occurrence is much lower around such stars. The outcomes of our prescription for external disc depletion show significant differences to the current approximation adopted in state-of-the-art population synthesis models, motivating future careful treatment of this important process.